(untitled) (Scientific journal of the Fergana State University, 2023)
This article is dedicated to the history of studying process by Turkestan youngsters in middle and high education centres of Ozarbayjan in the 20 s of the XX century. In this period Turkestan youngsters were sent to Germany, Russian and to the central cities of Ozarbayjan with the aim of preparing good specialists. In this article the archive documents and the articles which were published in National press of Turkestan related to the students who studied in Baku and Ganja were discussed.